PELAKSANAAN SUPERVISI OLEH PENGAWAS DI TK YAA BUNAYYA HIDAYATULLAH KUMAI - Musyarapah, Musyarapah; Wulan, Desty Angga (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
Abstract To improve the quality of education, supervision should be carried out as one of the real efforts of the guarantors of the quality of education. Supervision of early childhood education is an effort to assist and guide school principals and teachers to improve the quality of learning and early childhood education. However, when looking at the reality on the ground, a supervisor also has many drawbacks. Supervisors do not only carry out routine supervision because supervisors in Kumai District often experience problems with the distance to the schools they supervise. The purpose of this article is to let teachers and principals know that the task of a supervisor is not easy. They spend their time just to be able to make the school they foster a school with quality education. The research method used is descriptive qualitative by describing the implementation of kindergarten supervision. The subjects in this study were school supervisors from the Kumai District Education Office, principals and kindergarten teachers at Yaa Bunayya. The results of this study are the implementation of managerial supervision at Yaa Bunayya Kindergarten which includes evaluating the performance of the principal, infrastructure, and completeness of school administration which is carried out using monitoring and evaluation techniques. Implementation of academic supervision at Kindergarten Yaa Bunayya includes the completeness of RPPM (Weekly Learning Implementation Plan), RPPH (Daily Learning Implementation Plan), children's daily assessment, weekly assessment, monthly assessment, semester assessment, anecdotes, portfolio of children's work, assessment chart, calendar education, SOP, and so on.